Effect of ibuprofen on the establishment of the gestation of in vitro produced bovine embryos - Narváez Bedoya, Héctor Javier (2021)
The aim of this study was to evaluate the effect of the administration of ibuprofen in the establishment of the gestation of bovine embryos produced in vitro. In total, 85 Bos taurus x B. indicus heifers were used as embryo recipients, which were subjected to a protocol of synchronization of oestrus and ovulation with the insertion of an intravaginal progesterone implant (Sincrogest®) for eight days, plus the application of 2 mg of oestradiol benzoate (Sincrodiol®). To the removal of the implant, 500 μg sodium cloprostenol (Sincrocio®), 300 IU of equine chorionic gonadotropin (Sincro eCG®), plus the administration of 1 mg of oestradiol cypionate (SincroCP®,) were applied. One hour before embryo transfer, 5 mg/kg of ibuprofen IM was applied. No significant difference was observed in the gestation rate of the control group (47.5%) and the ibuprofen group (35.5%). It is concluded that the administration of ibuprofen in B. taurus x B. indicus heifers one hour before the transfer of the embryos in vitro had no effect on the establishment of gestation.